Analisis Pengaruh Investasi Modal dan Upah dalam Penyerapan Tenaga Kerja di Industri Anyaman Rotan Kota Palangka Raya - Febriani Silitonga; Sunaryo Neneng; Dedi Takari (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
Research on the speed of development economic growth in the rattan wicker industry during the COVID-19 pandemic aims to analyze that the value of capital investment and wages has a significant effect on labor absorption in the rattan woven industry in the city of Palangka Raya. The benefits of this research can add knowledge and insight, especially how the industrial development of rattan woven in Palangka Raya City. The data used in this study are primary data and data collection was done by interviewing 25 respondents, the data that had been collected were processed and analyzed using multiple linear regression. The results showed that the added value of investment, wages and capital together up to a confidence level of 80% had a significant effect on the employment of the rattan weaving industry in Palangka Raya City. In terms of the investment value variable, every time there is an increase in investment value of 1%, it can cause the increase in labor absorption to be 8.275%. Every 1% increase in the value of capital can cause the increase in labor absorption by 3.351%. Each 1% increase in the value of wages can cause the increase in labor absorption by 1.987%. For the handicraft industry in taking the given capital assistance, it is better to pay attention to the management of that capital. The need for financial records must also be considered so that there is transparency to various parties regarding capital and income. So that this research can be a reference in further research regarding the rate of economic growth which has an impact on other handicraft industries in Indonesia, so that this business remains sustainable